Synthesis of silver nanoparticles using aqueous root extract of Lantana camara and evaluation of antioxidant and antibacterial activities - Bhadel, Anita; Jaishi, Dipak Raj; Bhusal, Manisha; Chapagain, Keshav Raj; Pathak, Ishwor; Sharma, Sugam; Sharma, Khaga (BIBECHANA, 2026)
The present investigation employs an aqueous extract of Lantana camara for the eco-sustainable synthesis of silver nanoparticles. Because of their nanoscale dimensions, they exhibit distinctive physicochemical properties compared to bulk materials. Green synthesis is an approach for nanoparticle production that utilizes biological materials as reducing and stabilizing agents. This method is economical as well as eco-friendly.  Lantana camara is one of the popular medicinal plants. The present research focuses on the green synthesis of silver nanoparticles using an aqueous root extract of Lantana camara, along with their characterization and evaluation of antioxidant and antibacterial activity. This study involved characterizing silver nanoparticles using UV-Vis spectroscopy, XRD, FTIR, FE-SEM, and EDX techniques, along with evaluating their antioxidant and antimicrobial activities. The synthesized silver nanoparticles exhibited a maximum absorption peak at 408 nm and were spherical in shape with an average size of 5.98 nm. The IC50 of AgNPs is 32.49 ± 1.84 µg/mL, which shows the highest potential of the antioxidant activity of AgNPs than the plant aqueous extract. The ZOI value of green-synthesized silver nanoparticles is 8 mm for Staphylococcus aureus and 9 mm for Klebsiella pneumoniae where the root extract has a ZOI of 6 mm for Staphylococcus aureus and 5 mm for Klebsiella pneumoniae. The synthesis of silver nanoparticles mediated by plant extracts has strong antioxidant potential that lessens oxidative stress in human cells and eventually may help to prevent cancer and for the development of new medications.